The contributions of Arabic in classic Indonesian Literature in Hamzah’s Poetry - Cahya Buana; Ahmadi Usman (دراسات فی اللغه العربیه و آدابها)
Historical literature in Indonesia has indicated that it has been influenced in ages by foreign literature, especially Arabic literature. However, this perspective requires more evidence, therefore it could indicate the validity of the influence of old Indonesian literature by Arabic literature and in several aspects. This study intends to reveal the influence of old Indonesian literature by Arabic literature through the poetry of Hamzah Fansuri, a very famous Sufi poet from Aceh. Hamzah Hansuri is known as a follower of the Wahdatul concept pioneered by Ibn Arabi. He is a scholar who first introduced the form of poetry in Malay literature. In composing his verses, it is indicated indicates that they were influenced by Arabic literature. Through a comparative literary study between Arabic literature and Indonesian literature, it can be concluded that the poetry composed by Hamzah Fansuri is influenced by Arabic literature’s aspect, such as terms of language, form and content. From the language aspect, Hamzah Fansuri's verses contain a lot of Arabic vocabularies, most of which have been adapted into Indonesian such as thalib, ghaib, taib, syair, madah,i’tiqad ect. From the form’s aspect, Hamzah Fansuri’s verses indicate several elements in Arabic literature, such as ‘arūḍ, qāfiyah, balāgah, iqtibās, and others. On the content basis, Hamzah Fansuri’s verses are influenced by various kinds of Arabic Sufism, such as Ibn Arabi and others. Thus, Hamzah Fansuri also proved well many innovations in his verses, either the form or content according to Indonesian’s context.